Empirical model for predicting the inside air temperature of a naturally ventilated greenhouse with tomato crop, under hot and arid climates - K MESMOUDI; P E BOURNET; A BRIMA; H BENMOUSSA (Journal of Renewable Energies, 2017)
The energy balance components of a greenhouse as well as the greenhouse design may strongly impact the greenhouse energy. Few studies were devoted to the description of the energy balance components of a greenhouse located in the semi arid region of the southern Mediterranean basin, and no attention was paid to the prediction of the inside air temperature. In this study, experiments were undertaken to investigate the response of a greenhouse to the outside climate conditions considering a naturally ventilated Venlo glasshouse with a tomato crop. The measurements show that the difference between inside and outside air temperature is strongly linked to the incoming solar radiation as well as to the wind speed. From these results a simplified model was established to predict the greenhouse air temperature, knowing the greenhouse characteristics and the outside climate variables. The model is based on the energy balance of the greenhouse. Using a parameter identification technique, the model was calibrated against the experimental results. A sensivity analysis was conducted to assess the impact of several physical parameters such as solar radiation, wind speed and cover transmission on the evolution of the inside air temperature. This model appears to be suitable for predicting the greenhouse air temperature satisfactorily.